2017
DOI: 10.1038/srep43774
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid resistance of migration and gene expression in a daughter MDA-MB-231 breast tumour cell line selected for high metastatic potential

Abstract: Glucocorticoids are commonly used to prevent chemotherapy-induced nausea and vomiting despite a lack of understanding of their direct effect on cancer progression. Recent studies suggest that glucocorticoids inhibit cancer cell migration. However, this action has not been investigated in estrogen receptor (ER)-negative breast tumour cells, although activation of the glucocorticoid receptor (GR) is associated with a worse prognosis in ER-negative breast cancers. In this study we have explored the effect of gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 59 publications
4
27
0
1
Order By: Relevance
“…Since it has been reported that the anti-inflammatory agent dexamethasone inhibits MMP-2 expression [ 27 , 29 ] and cancer cell migration [ 38 40 ], we examined the effect of dexamethasone on ATRA-induced MMP-2 secretion in THP-1 cells. The cells were pretreated with dexamethasone at different concentrations for 2 h, followed by ATRA treatment for 48 h. The culture supernatants were concentrated and subjected to western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Since it has been reported that the anti-inflammatory agent dexamethasone inhibits MMP-2 expression [ 27 , 29 ] and cancer cell migration [ 38 40 ], we examined the effect of dexamethasone on ATRA-induced MMP-2 secretion in THP-1 cells. The cells were pretreated with dexamethasone at different concentrations for 2 h, followed by ATRA treatment for 48 h. The culture supernatants were concentrated and subjected to western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The non-essential role of PR that we observed in the inhibition of migration of breast cancer-derived cells in response to progesterone, specifically in the PR-negative MDA-MB-231, ZR-75-1 and BT-549 cells, may be mediated by interaction of progesterone with the glucocorticoid receptor (GR) or the membrane progesterone receptor (mPR), as has been reported before [ 22 , 24 , 25 ]. Of note, it has also been reported that treatment with glucocorticoids may similarly decrease the migration of PR-negative MDA-MB-231 cells [ 26 ], which suggests that redundant pathways may underlie the progesterone response in a PR-independent manner [ 27 ]. Consistent with these observations, we found that blocking PR by mifepristone prior to exposing the cells to progesterone did not rescue the effect of progesterone, suggesting that the progesterone-mediated suppression of migration in breast cancer cells is predominantly mediated in a PR-independent manner (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Prominent metabolic side effects of glucocorticoid treatment might be ascribed to transactivation of GRα 54 . In contrast, positive effects of glucocorticoids include reduced migration and a reduction in proteins associated with chemotherapy resistance in TNBC cells, which might be explained by transrepression of GRα [55][56][57] .…”
Section: Discussionmentioning
confidence: 96%